EFEKTIVITAS SEED COATING BERBAHAN AKTIF JAMUR ANTAGONIS MENGENDALIKAN PENYAKIT REBAH KECAMBAH PADA BIBIT CABAI - Mulyani, Rahmawati Budi; Riak Asie, Erina; Oemar, Oesin; Melhanah, Melhanah; , Rima (Politeknik Negeri Lampung., 2024)
This study aims to determine the inhibitory ability of antagonistic fungi from the rhizosphere of pepper (Piper nigrum L.), betel nut (Piper bettle L.) and Bawang Suna (Allium cinense G.Don.) against Fusarium oxysporum capsici which causes damping off disease and its effectiveness as a seed coating against damping off disease in chili seedlings. The research was carried out in the laboratory and experimental garden of the Department of Agricultural Cultivation, Faculty of Agriculture, UPR. Testing the antagonistic inhibition of F.o.capsici in vitro, where the antagonistic fungus with the highest inhibition from each plant rhizosphere was used as a seed coating for chili seeds to determine its effectiveness in suppressing damping off disease on seedlings. The results of the study obtained nine antagonist fungi with very good inhibition against the pathogen F.o.capsici in vitro ranging from 70.36 – 77.74%. Three types of antagonistic fungi that are used as active ingredients in seed coatings are Gliocladium sp. from pepper rhizosphere (73.53% inhibition), Penicillium citrinum from betel rhizosphere (77.74% inhibition), and Trichoderma harzianum from suna onion rhizosphere (70.83%). The seed coating treatment with active ingredients from three types of biological agents significantly reduced the intensity of damping off disease (0%) compared to the control (23.75%). Control effectiveness reaches 100% with very good category. Seed coating with active ingredients of T. harzianum and Gliocladium sp was able to increase plant height by 34.06% and 43.11%, respectively, but there was no significant difference in increasing the number of leaves. Seed coating treatment with biological agents effectively protects seeds and plant seedlings from attack by pathogens F.o. capsici through mechanisms such as antibiosis, parasitism and competition, besides that rhizosphere fungi can induce plant resistance and produce growth regulators which can increase the growth of chili seedlings. It is hoped that in the future the seed coating treatment added with biological agents can replace the use of chemical pesticides in controlling soil-infected diseases